An environmental comprehensive study of the soil of Al- Wusta Governorate in Gaza strip - Nusair, Fadi Rafeeq (Journal of agricultural, environmental and veterinary sciences, 2020)
The research dealt with the study of the soil of the Alwusta governorate in terms of geographical and astronomical location and administrative division, and an applied study of the soil for some of the physical characteristics of it, the tissue where it was found that the plumatic soil is the most prevalent type of soil and constitutes more than 50.4% of the study area, and the governorate suffers from a poverty in the organic matter where Its ratio is 55.6% between poor and medium, and the soil of the study area is characterized by high humidity, as well as dealing with chemical properties, including calcium carbonate, which is characterized by its poverty in the soil, where the proportion of the poor soil with calcium carbonate constitutes 86.6% between poor and medium, and we find that the soil A few gain of electrical conductivity where low electrical conductivity soil form 78.1% of the province area, but for the acidity of the soil, we find that the highly alkaline soil and constitute a gain of 75% of the province area and this shows that the soil tends to salinity.